Cancer in Lebanon: A Review of Incidence Rates from 2008 to 2015 and Projections Till 2025 - Khachfe, Hussein H.; Rahal, Zahraa; Sammouri, Julie; Kheil, Mira; Baydoun, Hussein; Chatila, Dana; Dirawi, Hiba; Fouad, Fouad M. (South Asian Journal of Cancer, 2020)
Background and Objectives Cancer carries one of the heaviest burdens globally in terms of mortality. Lebanon is a middle-income Middle East country also plagued with cancer, as such a study and analysis of cancer trends and projections would serve a great benefit in the fight against the disease.Materials and Methods All data pertaining to cancers in Lebanon were extracted from the National Cancer Registry of Lebanon Web site. Data were analyzed to produce trends over the years of our study (2008–2015). Ten-year projections were further calculated for the top cancers by the primary site using logarithmic models.Results The top cancers in Lebanon are the breast, lung, colorectal, bladder, and prostate. The top cancers affecting females are the breast, lung, and colorectal. The top cancers affecting males are the prostate, lung, and bladder. Cancer cases are projected to increase in Lebanon over the next 10 years.Conclusion Lebanon had a steady incidence rate of cancer cases during the time of our study. A more complete understanding of cancer trends and their ultimate reduction will require further research into the origins of specific cancers and the means of prevention and control.
Keywords: cancer; epidemiology; Lebanon; Middle East; neoplasia; North Africa